Microglial Activation on 11C-CB184 PET in a Patient With Cerebellar Ataxia Associated With HIV Infection. (March 2018) - Ishibashi, Kenji; Miura, Yoshiharu; Imamura, Akifumi; Toyohara, Jun; Ishii, Kenji
Abstract : Abstract: A 63-year-old man complaining of prolonged imbalance underwent 11 C-CB184 PET to assess microglial activation 3 years after being diagnosed with cerebellar ataxia associated with HIV infection. 11 C-CB184 images revealed significant cerebellar uptake where MRI signal abnormalities were observed at disease onset, although these abnormalities had mostly disappeared at the time of 11 C-CB184 PET. Microglia are believed to be a long-term reservoir for HIV infection, causing persistent immune activation (ie, chronic inflammation). Hence, in this case, increased 11 C-CB184 binding may reflect persistent microglial activation along with HIV persistence in the cerebellum. However, further pathological investigations are desired to validate 11 C-CB184 PET.